A case of relapsed visceral Kaposi's sarcoma with bilateral chylothoraces successfully treated with paclitaxel. (July 2015) - Natarajan, Pavithra; Miller, Alastair
Chylothorax is a rare complication of visceral Kaposi's sarcoma. We report a case with bilateral chylothoraces secondary to relapsed visceral Kaposi's sarcoma who was successfully treated with paclitaxel chemotherapy.